Recent Progress in Lunar Helium-3 Extraction Research - Olson, Aaron David Sumaili (Proceedings of the Wisconsin Space Conference, 2016)
Research is ongoing to develop a prototype lunar volatiles extraction system that will demonstrate a process for acquiring helium-3 for future fusion power plants that would produce little to no radioactive waste, and other volatile gases that can be used for life support in space. The prototype system is called the Helium Extraction and Acquisition Test bed (HEAT). Â Testing of HEAT will focus on obtaining information on the rate of 3He extraction possible and to what extent thermal energy recovery can be employed in this kind of volatile extraction system.Â Before demonstrating the evolution of 3He out of regolith simulant, simulant that is embedded to a known concentration must be available in order to gauge the performance of HEAT.Â An implantation device is being developed to implant helium into batches of JSC-1A regolith simulant for HEAT. The implantation device under development is referred to as the Solar Wind Implanter (SWIM).